2015
DOI: 10.1038/ki.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Gluten exacerbates IgA nephropathy in humanized mice through gliadin–CD89 interaction

Abstract: IgA1 complexes containing deglycosylated IgA1, IgG autoantibodies, and a soluble form of the IgA receptor (sCD89), are hallmarks of IgA nephropathy (IgAN). Food antigens, notably gluten, are associated with increased mucosal response and IgAN onset, but their implication in the pathology remains unknown. Here, an IgAN mouse model expressing human IgA1 and CD89 was used to examine the role of gluten in IgAN. Mice were given a gluten-free diet for three generations to produce gluten sensitivity, and then challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 40 publications
(46 reference statements)
2
58
0
2
Order By: Relevance
“…Thus, the pathogenic association of DH with GSE is probably mediated by CD89. Our results maybeinlinewiththethesisofPapistaet al [22], whorevealedthatglutenexacerbatesIgAnephropathythroughgliadin-CD89interaction.Papistaet al [22] demonstrated that mice on a gluten-free diet lacked IgA1-CD89 complexes, and disease severi-tydependedonglutenandCD89.Itisknownthat aglutendietexacerbatescutaneousIgAdeposition, inflammation,andincreasedserumanti-npGandanti-tTG IgA antibodies. Thus, similarly to DH, the direct binding of the gluten-subcomponent gliadin to CD89 may aggravate DH development through inductionpathologicalimmuneresponse.…”
Section: A B C D E Fsupporting
confidence: 90%
“…Thus, the pathogenic association of DH with GSE is probably mediated by CD89. Our results maybeinlinewiththethesisofPapistaet al [22], whorevealedthatglutenexacerbatesIgAnephropathythroughgliadin-CD89interaction.Papistaet al [22] demonstrated that mice on a gluten-free diet lacked IgA1-CD89 complexes, and disease severi-tydependedonglutenandCD89.Itisknownthat aglutendietexacerbatescutaneousIgAdeposition, inflammation,andincreasedserumanti-npGandanti-tTG IgA antibodies. Thus, similarly to DH, the direct binding of the gluten-subcomponent gliadin to CD89 may aggravate DH development through inductionpathologicalimmuneresponse.…”
Section: A B C D E Fsupporting
confidence: 90%
“…At the opposite way, a gluten free diet during three generations in α1KI-CD89Tg mice, a humanized model of IgAN, resulted in a massive decrease of IgA1 deposits in kidney associated to the diminution of inflammation and haematuria [32]. These results were strong and reproducible (n=20 animals, 100% of animals).…”
Section: Animal Modelsmentioning
confidence: 81%
“…Moreover, gliadin binds also directly to mesangial cells in vitro [48] increasing polymeric IgA Moreover, gliadin directly interacts with CD89 and participates in the formation of IgA-sCD89 complexes. Purified gliadin bound to recombinant sCD89 in a dose-dependent way, as shown by ELISA and surface acoustic wave (Figure) [32]. …”
Section: In Vitromentioning
confidence: 83%
See 2 more Smart Citations